`a) x^2 + y^2 = 1`

`==> 2x + 2yy' = 0`

`==> 2yy' = -2x`

`==> y' = (-2x)/(2y) = (-x)/y`

`==> yy' = -x`

`==> y'y' + yy'' = -1`

`==> y'^2 + yy'' = -1`

`==> yy'' = -1 -y'^2`

`==> y'' = -(1+y'^2)/y`

`==> y'' = -(1+(-x/y)^2)/y = -(1+x^2/y^2)/y = -(y^2+x^2)/y^3`

`==> y'' = -1/y - x^2/y^3`

``

b)`y^2 + 2y= 2x-1`

`==> 2yy' + 2y' = 2 `

`==> y'(2y+2) = 2`

`==> y' = 2/(2y+2)= 1/(y+1)`

`==> (y+1)y' = 1`

`==> yy' + y' = 1`

`==> y'y' +yy'' + y'' = 0`

`==> yy'' + y'' = -y'^2`

`==> y''(y+1) = -y'^2`

`==> y'' = -(y'^2)/(y+1)`

`==> y'' = -(1/(y+1)^2)/(y+1) = -1/(y+1)^3`

``

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.